Effect of Cyclosporine and Rifampin on the Pharmacokinetics of Macitentan, a Tissue-Targeting Dual Endothelin Receptor Antagonist - Bruderer, Shirin (Springer US, 2011)
Macitentan is a dual endothelin receptor antagonist under phase 3 investigation in pulmonary arterial hypertension. We investigated the effect of cyclosporine (Cs) and rifampin on the pharmacokinetics of macitentan and its metabolites ACT-132577 and ACT-373898 in healthy male subjects. In addition, in vitro studies were performed to investigate interactions between macitentan and its active metabolite ACT-132577 with human organic anion-transporting polypeptides (OATPs). The clinical study (AC-055-111) was conducted as a two-part, one-sequence, crossover study. Ten subjects in each part received multiple-dose macitentan followed by multiple-dose co-administration of Cs (part A) or rifampin (part B). In the presence of Cs, steady-state area under the plasma concentration–time profiles during a dose interval (AUC(τ)) for macitentan and ACT-373898 increased 10% and 7%, respectively, and decreased 3% for ACT-132577. Steady-state AUC(τ) of macitentan and ACT-373898 in the presence of rifampin decreased 79% and 64%, respectively. For ACT-132577, no relevant difference in AUC(τ) between the two treatments was observed. Macitentan co-administered with Cs or rifampin was well tolerated. The complementary in vitro studies demonstrated no marked differences in uptake rates of macitentan and ACT-132577 between the wild-type and OATP over-expressing cells over the concentration range tested. Concomitant treatment with Cs did not have any clinically relevant effect on the exposure to macitentan or its metabolites, at steady-state. Concomitant treatment with rifampin reduced significantly the exposure to macitentan and its metabolite ACT-373898 at steady-state but did not affect the exposure to the active metabolite ACT-132577 to a clinically relevant extent.